1985
DOI: 10.1017/s0001566000004906
|View full text |Cite
|
Sign up to set email alerts
|

Resting Metabolic Rate in Monozygotic and Dizygotic Twins

Abstract: Abstract. In order to study the influence of heredity on resting metabolic rate (RMR), 20 monozygotic and 19 dizygotic male twin pairs aged 20.6 (SD 2.9) and 21.4 (SD 3.1) years, gave their consent to participate in the experiment. Fat free weight (FFW) was estimated from underwater weighing. RMR was measured by indirect calorimetry using an open circuit system. RMR was expressed as kJ • min -1 , kJ/m 2 • h _1 , kJ/kg • h" 1 and kJ/kgFFW • h" 1 . Significant intraclass coefficients were observed in MZ twins fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
26
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(29 citation statements)
references
References 15 publications
3
26
0
Order By: Relevance
“…In publications from Fontaine et al 26 and Bouchard et al, 27 genetic contributions to RMR are estimated. RMR was obtained by indirect calorimetry for 39 twin pairs in the ®rst study 26 and 58 twin pairs and 31 parent-child pairs in the second study.…”
Section: Rmr and Free Living Eementioning
confidence: 99%
See 1 more Smart Citation
“…In publications from Fontaine et al 26 and Bouchard et al, 27 genetic contributions to RMR are estimated. RMR was obtained by indirect calorimetry for 39 twin pairs in the ®rst study 26 and 58 twin pairs and 31 parent-child pairs in the second study.…”
Section: Rmr and Free Living Eementioning
confidence: 99%
“…In publications from Fontaine et al 26 and Bouchard et al, 27 genetic contributions to RMR are estimated. RMR was obtained by indirect calorimetry for 39 twin pairs in the ®rst study 26 and 58 twin pairs and 31 parent-child pairs in the second study. 27 Heritability estimates based on twice the difference between MZ and DZ correlations, and twice the parent-child correlations, suggest that about 40% of the variance in RMR, after adjustment for age, gender, body mass and body composition, may be heritable.…”
Section: Rmr and Free Living Eementioning
confidence: 99%
“…1 For example, it has been shown that the intra-class correlation coefficient for REE in monozygotic twins was much higher than that in dizygotic twins. 4 A large number of genes have been implicated in obesityrelated phenotypes. 5 Perhaps the best documented obesity gene polymorphism is in the FTO gene.…”
Section: Introductionmentioning
confidence: 99%
“…3 A familial aggregation was demonstrated for metabolic rate 4 and respiratory quotient (RQ), an indicator of CHOOX to FATOX. 5 Twin studies 6,7 suggested a genetic influence on resting metabolic rate. A linkage study in Pima Indians detected quantitative trait loci (QTLs) on chromosome 1p31 and 20q11.2 influencing 24-h respiratory quotient (24RQ).…”
Section: Introductionmentioning
confidence: 99%